Downstream industrial biotechnology : recovery and purification - Flickinger, Michael C. (John Wiley & Sons, 2013)
"Universities worldwide are establishing biomanufacturing centers, and demand is growing for a workforce trained in this discipline. Downstream Recovery and Purification is an affordable, accessible desk reference on biomanufacturing for professionals, instructors, and students. With information on equipment, process and facility design, cGMP operation, and regulatory compliance, it is based on Wiley's 7-volume Encyclopedia of Industrial Biotechnology, Bioprocess, Bioseparation, and Cell Technology and features more than 50 carefully selected articles. Students and professionals alike will value this practical guide"--